2014
DOI: 10.3390/ma7042605
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adipogenic and Decreased Chondrogenic Differentiation of Adipose Derived Stem Cells on Nanowire Surfaces

Abstract: Despite many advances in tissue engineering, there are still significant challenges associated with restructuring, repairing, or replacing damaged tissue in the body. Currently, a major obstacle has been trying to develop a scaffold for cartilage tissue engineering that provides the correct mechanical properties to endure the loads associated with articular joints as well as promote cell-scaffold interactions to aid in extracellular matrix deposition. In addition, adipogenic tissue engineering is widely growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…Recent studies have elucidated the potential application of silicon NWs and polycaprolactone NW surfaces in tissue engineering and bone regeneration by showing their capability to support adhesion and proliferation of cells with elongated morphologies [24] , [37] . Other studies [10] have demonstrated the advantages of NWs in magnetic biosensing, where biomolecules of interest are labeled for their detection and identification.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have elucidated the potential application of silicon NWs and polycaprolactone NW surfaces in tissue engineering and bone regeneration by showing their capability to support adhesion and proliferation of cells with elongated morphologies [24] , [37] . Other studies [10] have demonstrated the advantages of NWs in magnetic biosensing, where biomolecules of interest are labeled for their detection and identification.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the plasma treatment effect on the interactions between PCL NFs and cells, cell adhesion and proliferation studies were conducted. Prior to cell seeding, untreated and plasmamodified PCL NFs were sterilized by exposure to UV light for 30 min[55][56] . Afterwards, human foreskin fibroblast (HFF) cells were seeded onto different PCL samples in a 24-well plate at a density of 40,000 cells/100 µl of medium per sample.…”
mentioning
confidence: 99%
“…One method to address this issue is micropatterning. This technique has been done using biocompatible polymers such as PCL, that has been modified with nanowires in order to improve mechanical properties and serve as a pattern for proliferation and maintenance of ASCs (Trujillo and Popat, 2014). Poly (vinyl alcohol) (PVA) has also been micropatterned onto polystyrene plates to facilitate the adipogenesis of MSCs and to test the effect of cell density in this system (Lu et al, 2009).…”
Section: Potential Bioengineering Approaches To 3d Brown Adipogenesismentioning
confidence: 99%